(untitled) (Carte Romanze, 2021)
In the context of the preparatory work for the edition of Prose 2 of the Roman de Troie, the need for a new analysis of the witnesses has arisen, especially in light of some textual findings that seem to have overturned the perspective on the stemmatic position of the two most ancient codices. The essay undertakes a material, textual and linguistic examination, of one of them, the ms. Grenoble, Bibliothèque Municipale, 861 (263 Rés.), copied and signed by a certain Johannes de Stennis in 1298 during his detention in the prison of Padua.